1996
DOI: 10.1002/hep.510230641
|View full text |Cite
|
Sign up to set email alerts
|

The translational inhibitor cycloheximide represses growth factor depletion-induced apoptosis in an alb-SV40T transgenic rat liver cell line

Abstract: A transgenic rat line carrying the alb-SV40A of apoptosis. Described as a counterpart of mitosis, transgene has been described by this laboratory. Several apoptosis has been the focus of a large number of studcell lines have been established from the livers of two of ies since it was first described by Kerr et al. [1][2][3][4][5][6] Affecting these rats. One of these cell lines, L37, exhibits a large single or small groups of cells, apoptosis exhibits nuclear/cytoplasmic ratio and a well-differentiated cyto-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
4
1
Order By: Relevance
“…There has been a debate about whether ongoing translation is required for apoptosis induction to occur, with evidence from some experimental systems suggesting that apoptosis does not require de novo protein synthesis (29,33,36,38). Conversely, other reports have shown that de novo protein synthesis is required for the cells to become apoptotic in response to nutrient deprivation or steroids (8,9,34). Even though this conflict likely reflects differences in the multiple pathways which can trigger apoptosis, our results do not contribute to this debate, since translation was not inhibited for more than 8 h after induction of apoptosis began.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…There has been a debate about whether ongoing translation is required for apoptosis induction to occur, with evidence from some experimental systems suggesting that apoptosis does not require de novo protein synthesis (29,33,36,38). Conversely, other reports have shown that de novo protein synthesis is required for the cells to become apoptotic in response to nutrient deprivation or steroids (8,9,34). Even though this conflict likely reflects differences in the multiple pathways which can trigger apoptosis, our results do not contribute to this debate, since translation was not inhibited for more than 8 h after induction of apoptosis began.…”
Section: Discussioncontrasting
confidence: 77%
“…Since the components of the execution machinery of apoptosis, i.e., the caspases, are already present in the cell at induction, de novo protein synthesis is not required for induction of apoptosis in most systems (29,33,36,38). On the other hand, it has been reported that in some cases, protein synthesis was necessary to induce apoptosis when nutrient deprivation or sterols were used to induce apoptosis (8,9,34). In these systems, expression of certain factors was necessary for induction of apoptosis, and apoptosis could be repressed by addition of translation inhibitors such as cycloheximide (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, p53-induced apoptosis has been shown to require new protein synthesis in order for the full program to be completed (Polyak et al, 1997). Similarly, nutrient deprivation (Bulera et al, 1996;Schulz et al, 1996), ionizing radiation (our unpublished results), and nonsteroidal anti-in¯ammatory drugs (NSAIDs) (Chan et al, 1998)-induced apoptosis can be inhibited by cycloheximide suggesting that ongoing protein synthesis is needed.…”
Section: Caspase-mediated Cleavage Of Eif4gmentioning
confidence: 82%
“…36 The observed dependence of NAHO27-induced apoptosis on overexpression of Bcl-2 (an anti-apoptotic protein of the intrinsic pathway) and on overexpression of smac/DIABLO (a pro-apoptotic mitochondrial protein) 37 further confirmed that NAHO27-induced apoptosis follows the intrinsic pathway – in line with the observation that apoptosis induction is slightly suppressed in the presence of NAC as a ROS-suppressing agent. Using cycloheximide (an inhibitor of transcriptional-steered apoptosis) 38–40 we could show that NAHO27-induced apoptosis is influenced by transcriptional or translational changes. And by means of gene expression analysis, we detected a 9-fold up-regulation of the pro-apoptotic harakiri gene in lymphoma cells treated with NAHO27.…”
Section: Discussionmentioning
confidence: 99%